Public-Access Defibrillation in Sudden Cardiac Arrest (Short Review) - Vyacheslav A. Vostrikov; Artem N. Kuzovlev (Общая реаниматология)
A public-access defibrillation is one of key techniques for improvement of the pre-hospital and in-hospital resuscitation success and survival rates of resuscitated patients in the case of a sudden cardiac arrest caused by ventricular fibrillation and ventricular tachycardia. The short review discusses the relation between the type of a sudden cardiac arrest and the survival rate, the 'chain of survival' concept and the role of early defibrillation, as well as the function of public-access defibrillation programs and the contribution of automated external defibrillators in prehospital and in-hospital resuscitation. In conclusion, the perspectives of introduction of the public-access defibrillation in Russia are discussed.